Aberrant Exon 8/8a Splicing by Downregulated PTBP (Polypyrimidine Tract-Binding Protein) 1 Increases CaV1.2 Dihydropyridine Resistance to Attenuate Vasodilation. Issue 10 (October 2020) - Lei, Jianzhen; Liu, Xiaoxin; Song, Miaomiao; Zhou, Yingying; Fan, Jia; Shen, Xiaowei; Xu, Xiaohan; Kapoor, Isha; Zhu, Guoqing; Wang, Juejin
Abstract : Objective: Calcium channel blockers, such as dihydropyridines, are commonly used to inhibit enhanced activity of vascular CaV 1.2 channels in hypertension. However, patients who are insensitive to such treatments develop calcium channel blocker-resistant hypertension. The function of CaV 1.2 channel is diversified by alternative splicing, and the splicing factor PTBP (polypyrimidine tract-binding protein) 1 influences the utilization of mutually exclusive exon 8/8a of the CaV 1.2 channel during neuronal development. Nevertheless, whether and how PTBP1 makes a role in the calcium channel blocker sensitivity of vascular CaV 1.2 channels, and calcium channel blocker-induced vasodilation remains unknown. Approach and Results: We detected high expression of PTBP1 and, inversely, low expression of exon 8a in CaV 1.2 channels (CaV 1.2E8a ) in rat arteries. In contrast, the opposite expression patterns were observed in brain and heart tissues. In comparison to normotensive rats, the expressions of PTBP1 and CaV 1.2E8a channels were dysregulated in mesenteric arteries of hypertensive rats. Notably, PTBP1 expression was significantly downregulated, and CaV 1.2E8a channels were aberrantly increased in dihydropyridine-resistant arteries compared with dihydropyridine-sensitive arteries of rats and human. In rat vascular smooth muscle cells, PTBP1 knockdown resulted in shifting of CaV 1.2 exon 8 to 8a. Using patch-clamp recordings, we demonstrated a concomitant reduction of sensitivity of CaV 1.2 channels to nifedipine, due to the higher expression of CaV 1.2E8a isoform. In vascular myography experiments, small interfering RNA-mediated knockdown of PTBP1 attenuated nifedipine-induced vasodilation of rat mesenteric arteries. Conclusions: PTBP1 finely modulates the sensitivities of CaV 1.2 channels to dihydropyridine by shifting the utilization of exon 8/8a and resulting in changes of responses in dihydropyridine-induced vasodilation. Abstract : Supplemental Digital Content is available in the text.